(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The present research investigates the relationship between achievement motivation and performance anxiety among university-level team and individual sports players. Sports performance depends not only on physical ability but also on psychological attributes such as motivation and anxiety regulation. The study aimed to explore how these psychological constructs vary across sport types and genders and to identify their interrelationship. A sample of 200 university players (100 team players and 100 individual players) was selected from affiliated colleges of Savitribai Phule Pune University. Standardized scales measuring achievement motivation and performance anxiety were administered. Descriptive statistics, t-tests, and Pearson correlation were used for analysis. The results revealed that individual sports players exhibited significantly higher achievement motivation but also experienced higher levels of performance anxiety compared to team players. A moderate negative correlation was found between achievement motivation and performance anxiety, indicating that highly motivated athletes tend to manage anxiety better. Gender differences were minimal, though male athletes scored slightly higher in achievement motivation, while female athletes reported marginally higher anxiety. The findings suggest that sport type significantly influences the psychological profiles of athletes. Coaches and sports psychologists can utilize these insights to design mental training programs that enhance motivation while managing competitive stress. The study contributes to sports psychology by emphasizing the dynamic relationship between motivation and anxiety as determinants of athletic performance.